Open-ended Questions and Mixed-mode Survey? A Comparison between Telephone Survey and Online Survey - Abuljadail, Mohammad (The Arab Journal of Administration, 2023)
The emergence of Internet has help surveyors create online survey methodology which had advantages and disadvantages. One of the online survey disadvantages is its difficulty in applying it on a random sample. Therefore, many researchers complement the disadvantages in any survey mode by using another mode. Although the use of mixed-mode became the new norm, previous studies have raised questions about the measurement of the questions and its reliability in measuring the same answers in two different modes. This study investigates one particular type of survey questions (open-ended) and compare the item-response rate between two groups of participants that responded to the survey through two different modes (telephone and online). The findings of the study show significant difference between the two groups in the item-response rate of open-ended questions. Online participants answer more open-ended questions than telephone participants. The study offers suggestions for future research and discusses the limitations in this study.